2023
DOI: 10.24912/ja.v27i1.1118
|View full text |Cite
|
Sign up to set email alerts
|

Green Accounting And Intellectual Capital Effect On Firm Value Moderated By Business Strategy

Abstract: This study aims to compare the influence of Green Accounting and Intellectual Capital on the Firm Value model with Business Strategy as a Moderating Variable, using 2016 to 2021 data from IDX in the Automotive and Components and Consumer Goods sector. This study used purposive sampling and hypothesis testing using multiple regression. Green Accounting is measured by obtaining an ISO 1400, Intellectual Capital by VAICTM and Business Strategy by PPC. The results show green accounting has a negative effect on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
2
0
3
Order By: Relevance
“…In addition to the relationship between GIC and company performance, based on the research results of Anggriani & Dewi (2021) and Chandra and Augustine (2019) simultaneously GIC, Corporate Social Responsibility costs, and Company Size affect company performance. Business strategy moderates the relationship between green accounting and intellectual capital on firm value (Gantino et al, 2023). Lastanti and Augustine's research (2022) which included the moderating variable of good corporate governance (GCG), showed that GCG could not moderate GIC on company performance.…”
Section: Company Performancementioning
confidence: 99%
“…In addition to the relationship between GIC and company performance, based on the research results of Anggriani & Dewi (2021) and Chandra and Augustine (2019) simultaneously GIC, Corporate Social Responsibility costs, and Company Size affect company performance. Business strategy moderates the relationship between green accounting and intellectual capital on firm value (Gantino et al, 2023). Lastanti and Augustine's research (2022) which included the moderating variable of good corporate governance (GCG), showed that GCG could not moderate GIC on company performance.…”
Section: Company Performancementioning
confidence: 99%
“…(Allen et al, 2023). Selain itu, penelitian telah menunjukkan bahwa akuntansi hijau dan modal intelektual dapat memiliki pengaruh yang signifikan terhadap nilai perusahaan, yang dimoderasi oleh strategi bisnis (Gantino et al,(2023). Beberapa peneliti lain seperti, Dura & Suharsono (2022) memberikan hasil pada penelitiannya, Akuntansi hijau memiliki dampak pada pembangunan berkelanjutan, akuntansi hijau memiliki dampak pada kinerja keuangan, akuntansi hijau memiliki dampak kinerja keuangan pada pembangunan berkelanjutan.…”
Section: Pendahuluanunclassified
“…Banyaknya penelitian yang saat ini membahas Green Intellectual Capital (GIC) dan Green Accounting menandai sebuah momentum penting dalam perjalanan ke arah bisnis yang lebih berkelanjutan. Seiring dengan meningkatnya kesadaran akan dampak lingkungan dan sosial dari kegiatan bisnis (Alvino et al, 2021), para peneliti dari berbagai bidang telah memusatkan perhatian mereka pada bagaimana dua konsep ini dapat memberikan kontribusi signifikan terhadap keberlanjutan usaha (Gantino et al, 2023).…”
Section: Pembahasanunclassified
“…The VAICTM method was chosen because this method is more effective in assessing IC which consists of capital employed/ physical capitals, human capitals, structural capitals, this calculation method can be obtained in the financial reports. Based at stakeholder theory, good management of IC elements adding more value and improving financial runs (Akram et al, 2023;Gantino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%